Ainda é rock? : a construção de identidades de jovens de Porto Alegre por meio de códigos visuais do rock - Queiroz, Fernando Pisoni (2019)
The present study aims to analyze how youngsters of generation Z of Greater Porto Alegre, not rockers, construct their identity from the identity codes of rock'n'roll. The basis for the research were references of Cultural Studies: Bauman (2005) and Hall (2000, 2003a) to conceptualize identity, representation and belonging; Kellner (2001), Shuker (1999) and Dayrrel (2001) to deal with rock history; and Silva (2003) as conceptual basis for imaginary. The research methodology includes a questionnaire survey of young radio programmers from Greater Porto Alegre to identify some aspects of the strategies currently adopted for the choice of musical style of radios; iconographic analysis of products from the websites of department stores Renner and C&A to identify the production of cultural consumer goods of rock and the signs of rock used as an argument for selling products; analysis of the consumption of musical genres in the music streaming service platform Spotify; analysis of the musical execution in the young radios of the capital gaúcha through the radio listening data of the Crowley Institute; public questionnaire, through two questionnaires, applied online - the first with the purpose of establishing a corpus composed of young people of the generation Z and the second one directed to the corpus willing to participate in the research, to identify tendencies of consumption and production of senses of the rock next to the respondents. Through this study, it was possible to verify that, for the researched youth, rock is a musical style. That band shirts, leather jackets, ripped jeans and piercings are some of the rock identity codes. Still, that the use of rock identity identities by artists/young people does not determine that the user is a rocker. Finally, these young people use rock codes in their identity construction.